2016
DOI: 10.1097/md.0000000000003195
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Different Initial Epinephrine Treatment Time Points on the Early Postresuscitative Hemodynamic Status of Children With Traumatic Out-of-hospital Cardiac Arrest

Abstract: The postresuscitative hemodynamic status of children with traumatic out-of-hospital cardiac arrest (OHCA) might be impacted by the early administration of epinephrine, but this topic has not been well addressed. The aim of this study was to analyze the early postresuscitative hemodynamics, survival, and neurologic outcome according to different time points of first epinephrine treatment among children with traumatic OHCA.Information on 388 children who presented to the emergency departments of 3 medical center… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 49 publications
(56 reference statements)
0
8
0
1
Order By: Relevance
“…Es wurden der 2020 PLS COSTR 1541 [ 143 ], sowie einige zusätzliche Nicht-RCT für den RR berücksichtigt (Anhang RR 30; [ 715 725 ]). Ein kürzeres Zeitintervall bis zur ersten Verabreichung von Adrenalin ist bei Kindern sowohl für Kreislaufstillstände im Krankenhaus (IHCA) als auch außerhalb des Krankenhauses (OHCA) mit einem günstigeren Outcome verbunden.…”
Section: Evidenzen Für Die Leitlinienunclassified
“…Es wurden der 2020 PLS COSTR 1541 [ 143 ], sowie einige zusätzliche Nicht-RCT für den RR berücksichtigt (Anhang RR 30; [ 715 725 ]). Ein kürzeres Zeitintervall bis zur ersten Verabreichung von Adrenalin ist bei Kindern sowohl für Kreislaufstillstände im Krankenhaus (IHCA) als auch außerhalb des Krankenhauses (OHCA) mit einem günstigeren Outcome verbunden.…”
Section: Evidenzen Für Die Leitlinienunclassified
“…Several studies have reported an OHCA survival rate of 6.7-10.2% and that at most 4% of patients have intact or functional neurological outcomes (1)(2)(3)(4)(5)(6)(7). Most pediatric survivors will have previously been subjected to high levels of physical or psychological stress from the resuscitation process and treatment procedures or even from the effects of high-dose drugs during their hospital stay (8)(9)(10)(11). Furthermore, postcardiac arrest syndrome and individual essential diseases (related to cardiac arrest) may potentially not only increase mortality during admission but also induce short/long-term postdischarge diseases (PDDs) (i.e., neurological defects, hypoxia-related organ dysfunction, and opportunistic infections) (10,(12)(13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…Since a high level of serum potassium changes the resting membrane potential and decreases the ability to reach the action potential, we suspect that the impact of hyperkalemia on the regulation of the heart rhythm would be more obvious during the early postresuscitation period (the first hour after achieving sustained return of spontaneous circulation (ROSC)). We also suspect that the postresuscitation heart function and hemodynamic status (i.e., blood pressure, heart rate, heart rhythm, and the amount of urine output) established by CPR might be more easily destroyed by hyperkalemia [ 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%